An Assessment of Covid-19 Pandemic Impact on Indonesian Tourism Sector - Atmojo, Muhammad Eko; Fridayani, Helen Dian (Journal of Governance and Public Policy, 2021)
This paper aims to analyze the impact of Covid-19 outbreak in term of tourism sector. The Covid-19 pandemic had a tremendous impact on all countries, one of it was Indonesia, that had been affected. Many sectors are affected, including tourism. A seriously affected in tourism is the micro, medium small enterprise or called MSME sector, this has a major influence on the rate of economic growth of the country, specifically in tourism sector. The existence of this pandemic, the tourism small and medium-sized enterprises experiencing huge losses, one of it is the lack of foreign tourists coming. The method used in the research is content analysis which analyze new in media that shown the topic related to Covid-19 and tourism. In contrast to previous studies, the decline in the number of tourists was due to the reach of tourist attractions, facilities, access, and costs, this study tries to look in more detail about how the Covid-19 pandemic has a serious impact on the tourism sector. As the result, the number of foreign tourist visits or foreign tourists to Indonesia has decreased in 2020 by 28.85% compared to the number of visits in 2019. Some areas such as Bali and Yogyakarta have lost both local and foreign tourists. This has an impact on MSME providers of travel, hotels, souvenir providers, regional handicrafts, and food and drink providers in tourist areas.